2019
DOI: 10.2478/s11756-019-00285-0
|View full text |Cite
|
Sign up to set email alerts
|

Pollinators and visitors of the generalized food-deceptive orchid Dactylorhiza majalis in North-Eastern Poland

Abstract: Pollinator foraging behavior plays a key role in breeding and therefore affects the evolution of the orchid reproductive strategy. Food-deceptive orchids usually implement a generalized plant pollination strategy and a relatively diverse group of pollinators visit them. Dactylorhiza majalis is a food-deceptive, early-flowering orchid that relies on insect-mediated pollination. This study's objectives were to identify D. majalis' pollinators and flower visitors and their foraging behaviors on D. majalis inflore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Indeed, the lack of specialization in pollinators is thought to be the major constraint on mimicry (Schiestl & Johnson, 2013). In the case of three studied Dactylorhiza, we observed different groups of pollinators (Ostrowiecka et al, 2019;A. Wróblewska, personal observation).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Indeed, the lack of specialization in pollinators is thought to be the major constraint on mimicry (Schiestl & Johnson, 2013). In the case of three studied Dactylorhiza, we observed different groups of pollinators (Ostrowiecka et al, 2019;A. Wróblewska, personal observation).…”
Section: Discussionmentioning
confidence: 61%
“…Pollination occurs in different taxonomic groups of insects (Hymenoptera, Diptera, and/or Coleoptera, Ostrowiecka et al., 2019; Wróblewska et al., 2019), which can promote cross‐pollination and/or geitonogamy (Hedrén & Nordström, 2009; Ostrowiecka et al., 2019). Moreover, the mechanism of spontaneous caudicle reconfiguration in three Dactylorhiza taxa exists, but results in less than 1% autogamous pollination in the studied populations (Tałałaj et al., 2019; Wróblewska et al., 2024).…”
Section: Methodsmentioning
confidence: 99%
“…The delayed pollinaria bending mechanism limited the events of geitonogamy, and the average rate of self-pollination tended to be higher in the rewarding orchids than in the deceptive orchids [ 32 ]. In any case, the data from the literature show that the bending mechanism limits but does not completely exclude the possibility of geitonogamy in deceptive orchids [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, recent investigations previously demonstrated that deceptive orchid species in Central Europe, depending on naive pollinators because not offering nectar, can increase their reproductive success by higher seed numbers in the face of a pollinator limitation (Sonkoly et al 2015). For an exact taxonomic identification of D. majalis pollinators and the floral chemical compounds attracting such insects, see Ostrowiecka et al (2019) and , respectively, and the literature cited therein.…”
Section: Continental Climate Stress Sexual Reproduction and Local Admentioning
confidence: 99%
“…III) The reduced embryo viabilitya trait likely attributable to possible inbreedingis also known to be an intrinsic genetic burden of allotetraploids hybrids under the condition of heterogeneic chromosomal recombination as pointed out at the start of the discussion. IV) Selfing, an extreme form of inbreeding, is unlikely due to the specific blossom morphology of D. majalis (Schoenichen 1940, experimentally shown by Vojtko et al 2015) and pollinaria bending (discussed in Ostrowiecka et al 2019). V) An elevated level of gene flow, counteracting possible inbreeding, will be expected with regard to the fact that the embryo is embedded into a surrounding scaffold of collapsed cork-like cells.…”
Section: What About Inbreeding and Gene Flow?mentioning
confidence: 99%